Influence of water transpired and irrigation on maize yields for future climate scenarios using Regional Model. (7th December 2021) - Donfack, Charveline F.; Wandjie, Brice B. S.; Efon, Eric; Lenouo, Andre; Monkam, David; Tchawoua, Clement
Abstract: Over northern Cameroon, limited water resources and drought conditions continue to hinder maize production. In this study, the result of the downscaling of the global climate model MPI‐ESM‐LR by the regional climate model REMO under the high‐emission Representative Concentration Pathway 8.5 scenario is used to force the agricultural model AquaCrop. The main goal of the study is to assess the climate change impact on maize yield production throughout the 21st century in this region. The model is first calibrated, and then validated, observed in situ precipitation, temperature, and yield data over the period 2005–2018. The results showed that if the amount of water increase over a period of 1 year by 27 mm, maize yield will increase by 0.415 ton/ha, which corresponds to more than 8% over the entire study area. These findings can be used for decision‐making by Cameroonian farmers, particularly in optimizing maize production under climate change scenarios. Irrigation potentially minimizes the impact of climate change. The result also reveals that, for a better yield of corn, the quantity of water necessary for irrigation would be less than 80 mm in 2099 in northern Cameroon. Abstract : Cameroon sub‐division map showing the localization of the study areas. Inset map showing the localization of Cameroon in Africa.